Mapping Research Trends on 21st-Century Problem-Solving Skills in Science Learning: A Literature Review from 2014 to 2023 - Syarful Annam; Amalia Syuzita; Rosi Pratiwi; Yusuf Sarkingobir (Research in Education, Technology, and Multiculture, 2024)
Abstract: Problem-solving skills are among the most important competencies of students, especially in the area of science education in the 21st century. Problem-solving skills enhance critical, logical, and creative thinking skills, which are necessary to solve complex real-life problems. This study is intended to identify and analyze research trends with regard to problem-solving skills in science learning from 2014 to 2023. A qualitative bibliometric approach has been used, and the data was collected using Publish or Perish and Dimensions.ai. In total, 200 documents indexed by Google Scholar were analyzed. Research trends, key keywords, and publication patterns were mapped and visualized using the VOSviewer software. The findings indicated that research on problem-solving skills gained consistent interest over the last decade, with the highest number of publications in 2023. Journals were the most common type of publication, followed by proceedings, chapters, and books. Among all publication venues, the Journal of Physics: Conference Series turned out to be the most important, publishing 784 articles and receiving 2567 citations. The most frequent keywords accompanying research in problem-solving are "critical thinking," "science learning," "motivation," and "teacher," which point to the interdisciplinary nature of the topic. Bibliometric visualization shows the emergence of new research clusters: student skills development, teaching strategies, and assessment methods. The conclusion from this study is that, while the research on problem-solving skills has grown steadily in science education, the implementation of practical teaching strategies in a classroom to enhance these skills remains fragmented. The future direction for research should encompass experimental studies through the integration of problem-based learning approaches that are important in the development of critical and creative thinking among students. Such findings have an important basis for educators, policymakers, and researchers to devise evidence-based practices that enhance the outcomes of science education.     Keywords: problem-solving skills, 21st-century competencies, science learning, bibliometric analysis, critical thinking.